The Impact of the Covid-19 Pandemic on the Critical Thinking Skills of High School Students - Anggriani, Nigia Deta; Purwoko, Agus Abhi; Al Idrus, Syarifa Wahida (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2023)
This research is a descriptive research that aims to describe students’ critical thinking skills in chemistry during the Covid-19 pandemic. The Covid-19 pandemic carried out online learning, then transferred to limited face-to-face learning. The research sample was taken from a Mataram City High School consisting of 9 classes XI and XII. Determination of the sample is determined as much as 30% of the population (10 people from each class). Sampling was chosen randomly (draw lots) in each class. The research data is in the form of a chemical bond material description test whose validity and reliability have been tested. Data were analyzed descriptively in the form of percentages. The results of the analysis of students’ critical thinking values show various categories, namely the percentage of class XI is lower than class XII. Overall the highest obtained by students is in the less category. Likewise, class XI is lower than class XII in terms of indicators of critical thinking. A more detailed explanation is presented in this article.